Peningkatan Hasil Belajar Matematika Menggunakan Model Pembelajaran Problem Based Learning di Kelas XI IPA 1 SMAN 10 Medan - Zalmira Aidina Barus; Haryati Ahda Nasution; Nurhafni Siregar; Ummi Aulia; Abdul Latif (Journal on Education, 2024)
Students' poor performance in mathematics is influenced by the teacher's incompetence in designing an engaging learning environment. This study's overarching goal is to enhance the mathematical knowledge of SMA Negeri 10 Medan's IPA 1 students in the eleventh grade by using the Problem Based Learning paradigm. This study uses Classroom Action Research (PTK), a research technique that has been used in two research cycles. The four phases of research in each cycle are preparation, execution, evaluation, and reflection. In this study, 36 students (16 males and 20 females) from class XI IPA 1 of SMA Negeri 10 Medan participated. In order to gather data, we used observation and a 5-question fill-out exam. Percentage computations were used in the data analysis method. The research results showed that student learning outcomes in cycle I averaged 71.94 with classical completion at 55.55%. Meanwhile, learning outcomes in cycle II averaged 82.22 with classical completeness of 83.33%. Results show that classical learning outcomes have improved, leading us to believe that PBL (Problem Based Learning) Learning Model may help students in Science 1 of class XI at SMA Negeri 10 Medan learn more mathematics.